Performance Evaluation of Field Balers - Sandhya, Sandhya; Singh, Surendra; Dixit, Anoop (Journal of Agricultural Engineering, 2007)
The field balers have been recently introduced in India for recovery of the straw from the field. Two experiments were conducted for evaluating the performance of the balers in the field; one experiment was conducted in combine harvested field and another in the field where stubble shaver was operated after combine harvesting. The straw baler gave better performance in stubble shaver operated field as compared to combine-harvested field. The bale size varied slightly in the field. Weight of the bales varied from 20-27 kg for paddy straw and 7-12 kg for wheat straw, The density varied from 130-200 kg/mÂ³ for paddy straw and 39-61 kg/mÂ³ for wheat straw. Fuel consumption of baler was in the range of 5.0 to 5.5 I/h. The field capacity of baler was 0.36 ha/h for paddy crop.